2020
DOI: 10.1112/plms.12337
|View full text |Cite
|
Sign up to set email alerts
|

Dimension of ergodic measures projected onto self‐similar sets with overlaps

Abstract: For self-similar sets on R satisfying the exponential separation condition we show that the natural projections of shift invariant ergodic measures is equal to min{1, h −χ }, where h and χ are the entropy and Lyapunov exponent respectively. The proof relies on Shmerkin's recent result on the L q dimension of self-similar measures. We also use the same method to give results on convolutions and orthogonal projections of ergodic measures projected onto self-similar sets.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…Shmerkin [14] proved an analogous result for the L q dimension of self-similar measures in 2019. Using similar ideas, Jordan and Rapaport [8] extended Hochman's result mentioned above from self-similar measures to the projections of ergodic measures. Using this result, Prokaj and Simon [9,Corollary 7.2] proved that ESC also implies that formula (1.11) holds for graph-directed self-similar attractors on the line.…”
Section: Terminologymentioning
confidence: 87%
See 1 more Smart Citation
“…Shmerkin [14] proved an analogous result for the L q dimension of self-similar measures in 2019. Using similar ideas, Jordan and Rapaport [8] extended Hochman's result mentioned above from self-similar measures to the projections of ergodic measures. Using this result, Prokaj and Simon [9,Corollary 7.2] proved that ESC also implies that formula (1.11) holds for graph-directed self-similar attractors on the line.…”
Section: Terminologymentioning
confidence: 87%
“…We point out that we can select a suitable subsystem S F ⊂ S N F and form a graph-directed self-similar IFS from the functions of S F such that the attractor of this graph-directed system and Λ F coincide. Then we use the Jordan Rapaport theorem [12] to compute the dimension of this graph-directed attractor which, as we just mentioned, is the same as Λ F . In this way we obtain that dim H Λ F = s F .…”
Section: Introducing Continuous Piecewise Linear Ifssmentioning
confidence: 99%
“…To understand the general structure of the measure or the self-similar set K , one often considers basic dimensional quantities such as the Hausdorff dimension and analogous statements for measures, or other notions of dimension. Computing these values can be highly non-trivial for general iterated function systems of similarities and there is significant literature on this matter (see, for example, [2, 12, 16, 23, 26, 29, 32, 36]). In this paper, we focus on a more fine-grained notion of dimension known as the local dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Further progress on absolute continuity of Bernoulli convolutions was obtained by Varjú [48]. Jordan and Rapaport [19] showed that the dimension of the push-forward measure of any ergodic shift-invariant measure equals to the entropy over Lyapunov exponent ratio under the exponential separation condition. However, such strong results are unknown in the case when the IFS consists of general conformal maps.…”
Section: Introductionmentioning
confidence: 99%
“…One is the so-called place-dependent measures, which were studied by Fan and Lau [12], Hu, Lau and Wang [16], Jaroszewska [18], Jaroszewska and Rams [19], Kwiecińska and W. Słomczyński [22], Czudek [8] and others. Let {p i } i∈A be a family of Hölder continuous maps p i : I → [0, 1] such that i∈A p i ≡ 1.…”
Section: Introductionmentioning
confidence: 99%